Secondary battery manufacturing method

The method addresses resistance and rigidity issues in secondary batteries by using a gel polymer electrolyte with reduced binder content and an adhesive compound, resulting in improved adhesion and conductivity.

JP2025501640AActive Publication Date: 2025-01-22LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024539060
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-14
Filing Date
2023-01-13
Publication Date
2025-01-22
Estimated Expiration
2043-01-13

AI Technical Summary

Technical Problem

Existing secondary batteries face issues with increased resistance and decreased cell rigidity due to excessive binder use in ceramic coating layers, leading to electrode misalignment and safety concerns, while gel polymer electrolytes suffer from higher interfacial resistance and lower ionic conductivity.

Method used

A method involving the use of a gel polymer electrolyte composition with reduced binder content in the ceramic coating layer, combined with an adhesive containing a first oligomer compound, to bond electrodes and separators, and a specific ratio of inorganic particles and binder, which is cured to enhance adhesion and reduce resistance.

Benefits of technology

The method results in a secondary battery with reduced resistance, improved cell rigidity, and enhanced mechanical durability by preventing excessive binder-related issues and misalignment, while maintaining high ionic conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501640000001_ABST
    Figure 2025501640000001_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a secondary battery, the method including the steps of: manufacturing an electrode assembly in which electrodes and separators are alternately stacked, and an adhesive is applied to a surface of at least one of the electrodes and the separator to adhere the electrodes and the separator to each other; housing the electrode assembly in a battery case; injecting a gel polymer electrolyte composition into the battery case to impregnate the electrode assembly; and curing the gel polymer electrolyte composition, wherein the adhesive includes a first oligomer compound; the separator includes a porous substrate and ceramic coating layers disposed on both sides of the porous substrate, the ceramic coating layers including 92% by weight or more and less than 100% by weight of inorganic particles and more than 0% by weight and less than 8% by weight of a binder; and the gel polymer electrolyte composition includes a lithium salt, an organic solvent, a polymerization initiator, and a second oligomer compound.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0006031, filed on January 14, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a method for producing a secondary battery. [Background technology]

[0003] 2. Description of the Related Art Along with technological development and increasing demand for electronic devices, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, have been commercialized and are widely used.

[0004] The secondary battery may be manufactured, for example, by housing an electrode assembly in which electrodes and separators are alternately stacked in a battery case, injecting an electrolyte into the battery case, and sealing the battery case.

[0005] Here, the separator is generally formed by forming ceramic coating layers containing inorganic particles and a binder on both sides of a porous substrate. Here, the binder is generally contained in a large amount to easily bond the electrode and the separator, but in this case, there is a problem that the resistance increases due to the excessive use of the binder, and the energy density of the battery decreases due to the increase in the thickness of the separator.

[0006] If the binder content in the ceramic coating layer included in the separator is reduced in order to prevent the above problems, there is a risk of quality degradation, such as a decrease in the adhesion between the electrodes and the separator, which reduces the rigidity of the cell and causes the electrodes to become misaligned.

[0007] Meanwhile, liquid electrolytes, particularly ion-conductive organic liquid electrolytes in which salts are dissolved in non-aqueous organic solvents, have been mainly used as electrolytes for secondary batteries up to now. However, such liquid electrolytes have problems such as the possibility of leakage to the outside of the secondary battery, reduced safety, and reduced cell rigidity.

[0008] In view of this, research is being conducted to commercialize polymer electrolytes such as gel polymer electrolytes instead of liquid electrolytes. The gel polymer electrolyte has the advantages of being able to prevent electrolyte leakage to the outside of the secondary battery and having excellent cell rigidity. However, the gel polymer electrolyte has problems such as high interface resistance and low ionic conductivity compared to liquid electrolytes.

[0009] In this respect, there is a need to develop a secondary battery that simultaneously reduces the resistance of the secondary battery and improves the cell rigidity. Summary of the Invention [Problem to be solved by the invention]

[0010] One object of the present invention is to solve the problems described above, and to provide a method for manufacturing a secondary battery that can produce a secondary battery having reduced resistance and simultaneously improved cell rigidity and mechanical durability. [Means for solving the problem]

[0011] The present invention provides a method for manufacturing a secondary battery, the method including the steps of: manufacturing an electrode assembly in which electrodes and separators are alternately stacked, and an adhesive is applied to a surface of at least one of the electrodes and the separator to adhere the electrodes and the separator to each other; housing the electrode assembly in a battery case; injecting a gel polymer electrolyte composition into the battery case to impregnate the electrode assembly; and curing the gel polymer electrolyte composition, wherein the adhesive includes a first oligomer compound; the separator includes a porous substrate and ceramic coating layers disposed on both sides of the porous substrate, the ceramic coating layers including 92% by weight or more and less than 100% by weight of inorganic particles and more than 0% by weight and less than 8% by weight of a binder; and the gel polymer electrolyte composition includes a lithium salt, an organic solvent, a polymerization initiator, and a second oligomer compound. Effect of the Invention

[0012] The method for manufacturing a secondary battery according to the present invention is characterized in that it manufactures a secondary battery including an electrode assembly in which electrodes and separators are alternately stacked, and a gel polymer electrolyte, the separator including inorganic particles and a binder in a specific content. Since the ceramic coating layer included in the separator includes a small content of binder, an increase in resistance due to an excessive amount of binder can be prevented, and the gel polymer electrolyte can compensate for the decrease in cell rigidity of the secondary battery that accompanies such a decrease in resistance. Therefore, the secondary battery manufactured by the method for manufacturing a secondary battery according to the present invention can reduce the resistance of the secondary battery and simultaneously improve the cell rigidity and mechanical durability by the combination of the above components.

[0013] In addition, the method for manufacturing a secondary battery according to the present invention is characterized in that an electrode assembly manufactured by alternately stacking electrodes and separators and bonding the electrodes and separators with an adhesive is housed in a battery case, and a gel polymer electrolyte composition is injected and cured to manufacture the secondary battery, wherein the adhesive includes a first oligomer compound. The adhesive includes a first oligomer compound, and the first oligomer compound can also participate in curing when the gel polymer electrolyte composition is cured. In addition, the first oligomer compound can bond the electrodes and the separator, and not only can it prevent a problem of misalignment of the electrodes and separators during the manufacture of the electrode assembly, but it can also be polymerized by curing the gel polymer electrolyte composition to improve the rigidity of the cell. [Brief description of the drawings]

[0014] [Figure 1] 2 is a schematic side view of an exemplary electrode assembly for explaining a manufacturing step of the electrode assembly in the manufacturing method of the secondary battery according to the present invention; FIG. [Diagram 2] 2 is a schematic plan view of a separator or an electrode for explaining a step of manufacturing an electrode assembly in a method for manufacturing a secondary battery according to the present invention; FIG. [Diagram 3] 4 is a schematic side view of a separator for explaining a step of manufacturing an electrode assembly in a method for manufacturing a secondary battery according to the present invention; FIG. [Figure 4] 4A to 4C are diagrams illustrating a method for manufacturing a secondary battery according to the present invention, and are views illustrating a manufacturing process of an electrode assembly. [Diagram 5] 4A to 4C are diagrams illustrating a method for manufacturing a secondary battery according to the present invention, and are views illustrating a manufacturing process of an electrode assembly. [Figure 6] 4A to 4C are diagrams illustrating a method for manufacturing a secondary battery according to the present invention, and are views illustrating a manufacturing process of an electrode assembly. [Figure 7] 4A to 4C are diagrams illustrating a method for manufacturing a secondary battery according to the present invention, and are views illustrating a manufacturing process of an electrode assembly. [Figure 8]4 is a view illustrating a step of accommodating an electrode assembly in the method for manufacturing a secondary battery according to the present invention; [Figure 9] 4 is a diagram illustrating a step of injecting a gel polymer electrolyte composition and impregnating an electrode assembly in the method for manufacturing a secondary battery according to the present invention; FIG. [Figure 10] FIG. 4 is a diagram for explaining a gel polymer electrolyte hardening step in the method for producing a secondary battery of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0016] In this specification, the average particle size (D 50 The average particle size (D) can be defined as the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured, for example, by using a laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron range to about several mm, and can provide results with high reproducibility and high resolution.

[0017] Hereinafter, the secondary battery of the present invention will be described in detail with reference to the drawings. When assigning reference numerals to components in each drawing, the same components may have the same numerals as much as possible even if they are shown in different drawings. In addition, when describing the present invention, if it is determined that a detailed description of related known configurations or functions may obscure the gist of the present invention, the detailed description may be omitted.

[0018] <Secondary battery manufacturing method> The present invention relates to a method for manufacturing a secondary battery, and more particularly to a method for manufacturing a lithium secondary battery.

[0019] The present invention provides a method for manufacturing an electrode assembly 100 in which electrodes 110, 120 and a separator 130 are alternately laminated, and an adhesive 140 is applied to a surface of at least one of the electrodes 110, 120 and the separator 130 to bond the electrodes 110, 120 and the separator 130 to each other, the steps of housing the electrode assembly 100 in a battery case 300, injecting a gel polymer electrolyte composition 200 into the battery case 300 to impregnate the electrode assembly 100, and hardening the gel polymer electrolyte composition 200. the adhesive 140 comprises a first oligomer compound, the separator 130 comprises a porous substrate 131 and ceramic coating layers 132a, 132b disposed on both sides of the porous substrate 131, the ceramic coating layers 132a, 132b comprising 92% by weight or more and less than 100% by weight of inorganic particles and more than 0% by weight and 8% by weight or less of a binder, and the gel polymer electrolyte composition 200 comprises a lithium salt, an organic solvent, a polymerization initiator, and a second oligomer compound.

[0020] (1) Manufacturing steps of electrode assembly Referring to Figures 1 and 2, first, an electrode assembly 100 is manufactured in which electrodes 110, 120 and separators 130 are alternately stacked, and an adhesive 140 is applied to the surface of at least one of the electrodes 110, 120 and the separator 130 to adhere the electrodes 110, 120 and the separator 130 to each other.

[0021] The electrode assembly 100 includes a plurality of electrodes 110, 120 stacked in a vertical direction P. The number of the electrodes 110, 120 may be two or more. In this specification, the term "vertical direction" may refer to a vertical direction based on the ground and is intended to describe the stacking direction of the electrodes, and is not intended to limit the angle of the stacking direction.

[0022] The electrodes 110, 120 may include a first electrode 110 and a second electrode 120. As shown in FIG. 1, the first electrode 110 and the second electrode 120 may be alternately stacked. The electrodes 110, 120 may be alternately stacked with a separator 130 in between. The first electrode 110 may be a positive electrode and the second electrode 120 may be a negative electrode. Or the first electrode 110 may be a negative electrode and the second electrode 120 may be a positive electrode. There may be one or more first electrodes and two or more second electrodes, respectively.

[0023] The first electrode 110 and the second electrode 120 may have a structure in which an active material slurry is applied to a current collector. The first electrode 110 and the second electrode 120 may have a structure formed by applying the active material slurry to both sides of a current collector, drying, and rolling. The active material slurry may be formed by stirring a granular active material, a conductive material, a binder, and the like in a solvent. The first electrode 110 and the second electrode 120 may use, without limitation, an active material, a conductive material, a binder, and the like used for a positive electrode or a negative electrode in the art.

[0024] The current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity. Specifically, the current collector can include at least one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, sintered carbon, and aluminum-cadmium alloy. For example, when the electrodes 110 and 120 are positive electrodes, the current collector used for the electrodes 110 and 120 can include aluminum, and when the electrodes 110 and 120 are negative electrodes, the current collector used for the electrodes 110 and 120 can include copper.

[0025] The current collector can be used in various forms such as a film, a sheet, a foil, a net, a mesh, a porous body, a foam, a nonwoven fabric, etc. The current collector can include a polymer layer and a metal layer disposed on both sides of the polymer layer, and the metal layer can include at least one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, sintered carbon, and an aluminum-cadmium alloy.

[0026] Specifically, when the electrodes 110 and 120 are negative electrodes, the negative electrode active material contained therein may be, for example, a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, the carbon material may be either low crystalline carbon or high crystalline carbon. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0027] Specifically, when the electrodes 110 and 120 are positive electrodes, the positive electrode active material contained therein is not particularly limited, and for example, the positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2O2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≦c2≦0.3); 2-c3 M c3 Examples of the positive electrode include, but are not limited to, lithium manganese composite oxides represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be a Li-metal positive electrode.

[0028] The binder contained in the electrode is a polyvinylidene fluoride polymer, polyvinyl alcohol, styrene butadiene rubber, polyethylene oxide, carboxyl methyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinylalcohol, cyanoethyl cellulose, cyanoethyl sucrose, cyanoethyl cellulose ... The binder polymer may be any one selected from the group consisting of sucrose, pullulan, polymethylmethacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, ethylene-vinyl acetate copolymer, polyarylate, and low molecular weight compounds having a molecular weight of 10,000 g / mol or less, or a mixture of two or more of these.

[0029] The conductive material contained in the electrode is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0030] An example of the thickener contained in the electrode is carboxymethyl cellulose (CMC).

[0031] 1 and 2, the electrode assembly 100 includes separators 130. The separators are stacked alternately with the electrodes.

[0032] As shown in FIG 1, the separator 130 may be bent or folded in a zigzag shape to wrap one end of the electrodes 110 and 120. For example, as shown in FIG 1, when the first electrode 110 and the second electrode 120 are alternately stacked, the separator 130 may be folded to wrap one end 110a of the first electrode 110, and then folded again to wrap one end of the second electrode 120 that is opposite to the one end 110a of the first electrode 110. By repeating such folding, the separator 130 may be bent or folded in a zigzag shape. The electrode assembly 100 may include one separator 130.

[0033] The electrode assembly 100 may be a zigzag stack type electrode assembly in which the separator 130 is bent or folded in a zigzag shape, and one or more basic units, in particular two or more basic units, in which the first electrode 110, the separator 130, the second electrode 120 and the separator 130 are stacked in order, are stacked.

[0034] As shown in FIG. 3, the separator 130 includes a porous substrate 131 and ceramic coating layers 132a, 132b disposed on both sides of the porous substrate.

[0035] The porous substrate 131 is not particularly limited as long as it is normally used as a separator for a secondary battery. Specifically, the porous substrate 131 is preferably one that has low resistance to ion migration of an electrolyte and has excellent electrolyte moisture absorption ability. More specifically, the porous substrate 131 may contain at least one selected from the group consisting of polyolefin resins such as polyethylene, polypropylene, polybutylene, and polypentene; fluorine resins such as polyvinylidene fluoride and polytetrafluoroethylene; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; polyacrylonitrile resins; and cellulose resins, and may be a porous film or nonwoven fabric containing any one or two or more copolymers or mixtures thereof, or a laminate structure of two or more layers thereof. The porous substrate 131 may be a porous film, nonwoven fabric, or a laminate structure of two or more layers thereof containing the polyolefin resin.

[0036] The size and porosity of the pores present in the porous substrate 131 are not particularly limited. Specifically, the porous substrate 131 may be a porous substrate containing pores having an average pore diameter of 0.01 μm to 1 μm, specifically 20 nm to 60 nm, with a porosity of 10 vol% to 90 vol%, specifically 30 vol% to 60 vol%, in which case it is preferable in terms of improving the mechanical strength of the porous substrate 131 and allowing ionic substances to move more smoothly between the positive and negative electrodes. The average pore diameter and porosity may be measured by analysis using a focused ion beam (FIB), a gas adsorption method, or a mercury intrusion method.

[0037] The thickness of the porous substrate 131 is not particularly limited, but may be, in consideration of appropriate mechanical strength as a separator and ease of movement of ionic substances, specifically, 1 μm to 100 μm, more specifically, 2 μm to 15 μm.

[0038] The ceramic coating layers 132 a and 132 b are disposed on both sides of the porous substrate 131 .

[0039] The ceramic coating layers 132a and 132b include inorganic particles and a binder. More specifically, the ceramic coating layers may consist of only the inorganic particles and the binder.

[0040] The inorganic particles may be introduced to prevent thermal shrinkage of the porous substrate at high temperatures and the resulting short circuit between the positive and negative electrodes, and the inorganic particles may serve as a kind of spacer that can maintain the physical shape of the porous substrate and minimize thermal shrinkage.

[0041] The inorganic particles can be used without any particular limitation as long as they are electrochemically stable in the operating voltage range of the battery (for example, 0 V to 5 V based on Li / Li+) and do not cause oxidation and / or reduction reactions, i.e., electrochemical reactions. The inorganic particles can be lithium phosphate (Li3PO4); lithium titanium phosphate (Lix Ti y (PO4)3, 0 < x < 2, 0 < y < 3); Lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), such as 14Li2O - 9Al2O3 - 38TiO2 - 39P2O5 of (LiAlTiP) x O y series glass (glass) (0 < x < 4, 0 < y < 13); Lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3); Li 3.25 Ge 0.25 P 0.75 such as lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5); Lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2); SiS2 - based glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4); P2S5 - based glass (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7); Al2O3; AlOOH; BaTiO3; BaSO4; MgO; CaO; CeO2; NiO; SiO2; SnO2; SrTiO3; TiO2; Y2O3; ZnO; ZrO2; Pb(Zr, Ti)O3 (PZT); Pb 1-x La x Zr 1-y Ti y O3 (PLZT); PB(Mg3Nb 2 / 3)O3-PbTiO3 (PMN-PT); hafnia (HfO2); a mixture of two or more of these. Specifically, the inorganic particles may be Al2O3; AlOOH; BaTiO3; BaSO4; MgO; CaO; CeO2; NiO; SiO2; SnO2; SrTiO3; TiO2; Y2O3; ZnO; ZrO2; Pb(Zr,Ti)O3 (PZT); Pb 1-x La x Zr 1-y Ti y O3(PLZT);PB(Mg3Nb 2 / 3 )O3-PbTiO3 (PMN-PT); hafnia (HfO2); a mixture of two or more of these, and more specifically, may include at least one selected from the group consisting of Al2O3; AlOOH; BaTiO3; BaSO4; and MgO.

[0042] The average particle size of the inorganic particles (D 50 ) can be 0.1 μm to 1 μm, specifically 0.2 μm to 0.7 μm.

[0043] The inorganic particles are included in the ceramic coating layers 132a and 132b in an amount of 92% by weight or more and less than 100% by weight. The content of the inorganic particles should be considered in relation to the content of the binder described below, and can be adjusted to prevent a decrease in thermal stability due to thermal contraction of the porous substrate and to prevent an increase in resistance due to an excessive amount of binder. Specifically, the inorganic particles can be included in the ceramic coating layers in an amount of 93% by weight to 98% by weight.

[0044] The binder may be included in the ceramic coating layers 132a and 132b to bind inorganic particles and to bind the separator and electrodes.

[0045] Here, the binder is contained in the ceramic coating layer in an amount of more than 0% by weight and less than 8% by weight. If the binder is contained in an amount of more than 8% by weight, the binder is excessively contained in the ceramic coating layer, which may cause an increase in the resistance of the secondary battery. On the other hand, if the binder is contained in the above range, there is a risk of a decrease in the cell rigidity of the secondary battery due to a decrease in the adhesive strength between the electrode and the separator. However, as described below, the present invention uses a combination of a separator having the above characteristics and a gel polymer electrolyte, and therefore can simultaneously achieve an improvement in the resistance of the secondary battery, as well as an improvement in cell rigidity and mechanical durability.

[0046] Specifically, the binder may be included in the ceramic coating layer in an amount of 2 wt % to 7 wt %, and when the amount is within this range, the binding force of the inorganic particles can be maximized and an increase in the resistance of the secondary battery can be prevented.

[0047] The binder may be a hydrophobic binder containing one or more hydrophobic functional groups in the molecule, such as a fluorine group (-F), an acrylate group (CH2=CHCOO-), a methacrylate group (CH2=C(CH3)COO-), a vinyl acetate group (-CH2=CHOCO-) or a nitrile group (-C≡N), or a hydrophilic binder containing one or more polar groups, such as a hydroxyl group (-OH), a carboxyl group (-COOH), a maleic anhydride group (-COOOC-), a sulfonic acid group (-SO3H) or an isocyanate group (-NCO), and any one or a mixture of two or more of these may be used. More specifically, the hydrophobic binder may be polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethylmethacrylate, polyacrylonitrile, polyvinylacetate, ethylene-vinylacetate copolymer, polyimide, polyethylene oxide, or the like.In addition, the hydrophilic binder may be cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, carboxyl methyl cellulose, polyvinyl alcohol, polyacrylic acid, polymaleic anhydride, polyvinylpyrrolidone, or the like.

[0048] Specifically, the binder may be an acrylic binder. The acrylic binder is well dispersed with the inorganic particles during the preparation of the ceramic coating layer, and thus the ceramic coating layer can be prevented from being separated into layers, with the binder in the upper layer and the inorganic particles in the lower layer. Such layer separation results in impeding ion migration in the negative and positive electrodes, causing an increase in resistance. Therefore, when an acrylic binder is used as the binder, the resistance reduction effect aimed at by the present invention can be exhibited at a more excellent level.

[0049] The acrylic binder may include at least one selected from the group consisting of a copolymer of ethylhexyl acrylate and methyl methacrylate; polymethylmethacrylate; polyethylhexylacrylate; polybutylacrylate; polyacrylonitrile; and a copolymer of butyl acrylate and methyl methacrylate.

[0050] The ceramic coating layer may contain inorganic particles and a binder in a weight ratio of 92:8 or more and less than 100:0, specifically 93:7 to 98:2.

[0051] The ceramic coating layers 132a and 132b may have a thickness of 0.1 μm to 10 μm, specifically 0.5 μm to 5 μm, and more specifically 1.0 μm to 2.5 μm. Since the ceramic coating layers 132a and 132b contain the binder in the above-mentioned small content, a separator with a thin thickness can be realized, and the energy density of the secondary battery can be further improved and low resistance can be achieved. The thickness of the ceramic coating layer may refer to the thickness of one ceramic coating layer formed on one surface of the porous substrate.

[0052] The ceramic coating layers 132a and 132b may be prepared by applying a ceramic coating layer forming composition, in which inorganic particles and a binder are dispersed in a solvent, to the porous substrate and drying the composition. The method of applying the ceramic coating layer forming composition is not particularly limited, and may be dip coating, die coating, roll coating, comma coating, gravure coating, etc., and more specifically, gravure coating may be used. The drying method after application of the ceramic coating layer forming composition may be natural drying, heat drying, hot air drying, etc.

[0053] The thickness of the separator 130 may be 1 μm to 20 μm, specifically 5 μm to 14 μm. According to the present invention, since the binder content in the ceramic coating layer is reduced, a separator with a thin thickness can be realized, and thus the energy density of the secondary battery can be further improved and low resistance can be achieved.

[0054] In the electrode assembly 100, an adhesive 140 is applied to a surface of at least one of the electrodes 110 and 120 and the separator 130, so that the electrodes 110 and 120 and the separator 130 are adhered to each other.

[0055] The adhesive 140 may be introduced to bond the electrodes 110, 120 and the separator 130. Specifically, the adhesive 140 may be introduced to fix the alignment position of the electrodes and the separator in the process of laminating, assembling, and stacking them in the manufacturing process of the secondary battery. As described above, the separator 130 according to the present invention has a reduced binder content, and therefore the adhesive strength between the electrodes and the separator may be insufficient during the manufacturing process of the secondary battery. The adhesive 140 compensates for this problem, easily bonds the electrodes and the separator, and prevents the separator from shifting during the manufacturing process of the electrode assembly, thereby improving the efficiency and quality of the process.

[0056] The adhesive includes a first oligomeric compound.

[0057] As used herein, "oligomeric compound" may refer to a compound in which about 10 or fewer monomers are polymerized, and the "oligomeric compound" may contain a crosslinkable group.

[0058] The first oligomer compound is included in the adhesive as an adhesive component for adhering the electrodes and the separator, and after being used as an adhesive component for the electrodes and the separator, the first oligomer compound can be dissolved and polymerized by injecting the gel polymer electrolyte composition to become a component of the gel polymer electrolyte.

[0059] The first oligomer compound may include at least one selected from the group consisting of polyether-based oligomers, polycarbonate-based oligomers, acrylate-based oligomers, polysiloxane-based oligomers, phosphagene-based oligomers, polyethylene-based oligomers, urethane-based oligomers, epoxy-based oligomers, fluorine-based oligomers, polyethylene oxide, polyester sulfide, polyvinyl alcohol, and polyvinylidene fluoride, specifically at least one selected from fluorine-based oligomers, polycarbonate-based oligomers, and polysiloxane-based oligomers.

[0060] For example, the fluorine-based oligomer may specifically include a unit derived from a fluorine-based monomer. The fluorine-based oligomer has the advantage that the fluorine-based functional group contained therein suppresses the generation of oxygen radicals caused by the decomposition of the positive electrode active material, thereby further improving the battery stability, and has excellent flame retardancy. More specifically, the fluorine-based oligomer may include at least one selected from tetrafluoroethylene (TFE)-vinyl acetate copolymer, (allyl 1,1,2,2-tetrafluoroethyl ether)-(2,2,2-trifluoroethyl acrylate) copolymer, tetrafluoroethylene-(2-vinyl-1,3-dioxolane) copolymer, and tetrafluoroethylene-vinyl methacrylate copolymer.

[0061] In addition, the polycarbonate oligomer has an affinity for the positive electrode, a structure similar to that of an organic electrolyte, and an advantage in that it has excellent ionic conductivity or ionic dissociation degree. The polycarbonate oligomer may be a polycarbonate having a weight average molecular weight of 1,000 g / mol to 50,000 g / mol, specifically 4,500 g / mol to 30,000 g / mol, more specifically 10,000 g / mol to 25,000 g / mol.

[0062] In addition, the polysiloxane oligomer can function as a scavenger for gases (such as HF) generated by side reactions of the electrolyte, thereby improving high-temperature storage characteristics.

[0063] The weight average molecular weight of the first oligomer compound may be from 1,000 g / mol to 50,000 g / mol, specifically from 4,500 g / mol to 30,000 g / mol.

[0064] The adhesive 140 is used to manufacture the electrode assembly 100 by adhering the electrodes 110, 120 and the separator 130, and after the electrode assembly 100 is housed in a battery case 300 and the gel polymer electrolyte composition 200 is injected into the battery case 300, the adhesive 140 may be dissolved in an organic solvent contained in the gel polymer electrolyte composition 200. Since the adhesive 140 according to the present invention is used to manufacture the electrode assembly 100 and then dissolved, it is possible to easily adhere the electrodes 110, 120 and the separator 130 without increasing the amount of binder in the separator 130, and also to prevent an increase in the thickness of the separator due to an increase in the amount of binder, thereby further improving the energy density of the secondary battery.

[0065] 2, the adhesive 140 may be applied in a plurality of patterns spaced apart from one another. Specifically, the adhesive 140 may be applied on a surface of at least one of the electrodes and the separator in a plurality of patterns spaced apart from one another. Specifically, the adhesive may be applied on a surface of at least one of the electrodes and the separator in a plurality of dots spaced apart from one another.

[0066] The application area of ​​the adhesive may be more than 0% and 1% or less, specifically 0.0001% to 0.05%, of the surface area where the separator and the electrode contact each other. This range is preferable because it allows the electrodes and the separator to be bonded with sufficient adhesive strength and prevents the adhesive from being applied in excess and remaining in the solvent without being dissolved, which causes an increase in resistance.

[0067] An exemplary method for manufacturing the electrode assembly will now be described with reference to FIGS.

[0068] Specifically, referring to Figures 4 to 7, the electrodes 110, 120 include a first electrode 110 and a second electrode 120, and the electrode assembly 100 can be manufactured by a method including the following steps (a) to (f).

[0069] (a) applying the adhesive 140 to at least a portion of the separator 130 and the first electrode 110; (b) adhering the separator 130 and the first electrode 110 with the applied adhesive 140; (c) folding one side of the separator 130 to cover the first electrode 110; (d) applying the adhesive 140 to at least a portion of the separator 130 and the second electrode 120; (e) adhering the separator 130 and the second electrode 120 with the applied adhesive 140; and (f) folding the other side of the separator 130 to cover the second electrode 120 .

[0070] 4, the adhesive 140 is applied to at least a portion of the separator 130 and the first electrode 110. The application of the adhesive 140 may be performed by applying the adhesive 140 to at least a portion of the separator 130 and the first electrode 110 using a first nozzle 1110. Although FIG. 4 illustrates the adhesive 140 being applied to the separator 130, the present invention is not limited thereto, and the adhesive 140 may be applied to at least a portion of the separator 130; the first electrode 110; or both the separator 130 and the first electrode 110.

[0071] Specifically, as shown in FIG. 4, the separator 130 may be unwound from a separator reel 630 and placed on the upper surface of a table 700 .

[0072] Referring to FIG. 5, the separator 130 and the first electrode 110 are bonded together by the applied adhesive 140 .

[0073] 5, the first electrode 110 may be formed by cutting a first electrode sheet 1101, which is wound from a first electrode reel 610, by a first cutter 810. Here, when a first transfer device 910 transfers the first electrode 110, a first header 1010 may adsorb the first electrode. Next, the first electrode 110 may be placed or disposed on the separator 130 as the first header 1010 and / or the table 700 move.

[0074] Referring to FIG. 6, one side of the separator 130 may be folded to cover the first electrode 110, and the adhesive 140 may be applied to at least a portion of the separator 130 and the second electrode 120.

[0075] After the first electrode 110 is attached on the separator 130, one side of the separator 130 is folded to cover the first electrode 110. For example, the separator 130 may be folded by moving the table 700 laterally.

[0076] Meanwhile, the adhesive 140 is applied to at least a portion of the separator 130 and the second electrode 120. The application of the adhesive 140 may be performed by applying the adhesive 140 to at least a portion of the separator 130 and the second electrode 120 using a second nozzle 1120. Although FIG. 6 illustrates the adhesive 140 being applied to the separator 130, the present invention is not limited thereto, and the adhesive 140 may be applied to at least a portion of the separator 130; the second electrode 120; or both the separator 130 and the second electrode 120.

[0077] Referring to FIG. 7, the separator 130 and the second electrode 120 are adhered to each other by the applied adhesive 140, and the other side of the separator 130 is folded to cover the second electrode 120.

[0078] A second electrode 120 is attached to the surface of the separator 130 opposite to the surface where the separator 130 and the first electrode 110 are in contact.

[0079] 7, the second electrode 120 may be formed by cutting a second electrode sheet 1201 unwound from a second electrode reel 620 by a second cutter 820. Here, when a second transport device 920 transports the second electrode 120, a second header 1020 may adsorb the second electrode. Then, as the second header 1020 and / or the table 700 move, the second electrode may be placed or adhered on the separator.

[0080] 7, after the second electrode 120 is attached, the other side of the separator 130 is folded to cover the second electrode 120. This makes it possible to manufacture an electrode assembly in which the first and second electrodes are alternately stacked, the separator is interposed between the first and second electrodes, and the separator is folded in a zigzag shape. Next, by repeating the above process, it is possible to realize an electrode assembly in which a plurality of first electrodes and second electrodes are alternately stacked.

[0081] Here, in the case of an electrode assembly including a separator folded in a zigzag shape as described above, the separator and / or electrode may be misaligned due to the folding or bending of the separator during the manufacturing process, which may lead to poor quality and reduced process efficiency, but according to the present invention, an adhesive is applied to bond the electrode and the separator, which can significantly prevent the above-mentioned misalignment of the electrode and / or separator, making it possible to manufacture a secondary battery with improved quality. The application of such an adhesive is particularly preferable in terms of complementing the adhesive strength of the separator in the present invention, which contains a low content of binder.

[0082] (2) Electrode Assembly Storage Step Referring to FIG. 8, the electrode assembly 100 is housed in a battery case 300 .

[0083] For ease of explanation, FIG. 8 shows a simplified representation of the electrode assembly.

[0084] The battery case 300 may be provided for the purpose of housing the electrode assembly 100 and the gel polymer electrolyte 200 .

[0085] The battery case 300 may be a pouch-shaped case made of a flexible material, for example, an aluminum pouch battery case.

[0086] When the battery case 300 is an aluminum pouch battery case, the battery case 300 can be formed of a pouch film in which, for example, a polypropylene layer (PP layer), an aluminum layer, and a polyethylene terephthalate layer (PET layer) are laminated in this order from the inside.

[0087] The battery case 300 may include a cup portion that is a receiving space for receiving the electrode assembly.

[0088] The battery case 300 may include a cover 310, and after the electrode assembly is housed and the gel polymer electrolyte composition is hardened and gelled, the battery case 300 may be sealed with the cover to manufacture a sealed secondary battery.

[0089] As shown in Fig. 8, a plurality of electrode tabs 400, 500 may be connected to the electrode assembly 100. Specifically, the plurality of electrode tabs 400, 500 may be connected to the electrodes 110, 120 of the electrode assembly 100, more specifically, the plurality of electrode tabs 400, 500 may be connected to the first electrode 110 and the second electrode 120, respectively, and may protrude to the outside of the battery case 300 to become a path through which electrons can move. In addition, in Fig. 8, the two electrode tabs 400, 500 are illustrated as being arranged in different directions with respect to the electrode assembly 100, but are not limited thereto, and may protrude in parallel in the same direction from one side of the electrode assembly 100. The plurality of electrode tabs 400, 500 may be positive electrode tabs and negative electrode tabs, and may be connected to the positive electrode and the negative electrode, respectively.

[0090] (3) Injection of gel polymer electrolyte composition and impregnation of electrode assembly 9, a gel polymer electrolyte composition 200 is injected into the battery case 300 to impregnate the electrode assembly 100. The gel polymer electrolyte composition 200 is impregnated into the electrode assembly 100, hardened, and disposed inside and outside the electrode assembly.

[0091] The gel polymer electrolyte 200a cured from the gel polymer electrolyte composition 200 has no fluidity, and since a gelled electrolyte is used, the cell rigidity of the secondary battery can be improved. In particular, the present invention makes it possible to realize a secondary battery with reduced resistance and improved cell rigidity by using the gel polymer electrolyte together with the above-mentioned separator. On the other hand, when the above-mentioned separator and liquid electrolyte are used, the cell rigidity is excessively reduced, which may lead to cell distortion, separator misalignment, and other problems that may lead to reduced processability and product defects, reduced safety, and the possibility of secondary battery explosion.

[0092] The gel polymer electrolyte composition 200 includes a lithium salt, an organic solvent, a polymerization initiator, and a second oligomeric compound.

[0093] The lithium salt can be used to provide lithium ions to a secondary battery.

[0094] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within a range of 0.1M to 5.0M, preferably 0.1M to 3.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore excellent electrolyte performance can be exhibited, and lithium ions can be effectively transferred.

[0095] The polymerization initiator may be used to polymerize the oligomer compound contained in the gel polymer electrolyte composition to form a polymer network bound to a three-dimensional structure.

[0096] The polymerization initiator can polymerize the oligomer compound by forming radicals by decomposition in the presence of heat or light. Specifically, the polymerization initiator can polymerize the second oligomer compound contained in the gel polymer electrolyte composition and the first oligomer compound dissolved by the gel polymer electrolyte composition after being used in assembling the electrode assembly.

[0097] The polymerization initiator may be a photopolymerization initiator or a thermal polymerization initiator depending on the polymerization method.

[0098] Specifically, the photopolymerization initiator may be, for example, 2-hydroxy-2-methylpropiophenone (HMPP), 1-hydroxy-cyclohexylphenyl-ketone, benzophenone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, oxy-phenylacetic acid 2-[2-iodo-2-phenyl-acetoxy-ethoxy]-ethyl ester, oxy-phenyl-acetic acid 2-[2-hydroxyethoxy]-ethyl ester, alpha-dimethoxy-alpha-phenylacetophenone, 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl ]-1-butanone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(eta5-2,4-cyclopentadiene-1-yl), bis[2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl]titanium, 4-isobutylphenyl-4'-methylphenyliodonium, hexafluorophosphate, and methylbenzoylformate.

[0099] Representative examples of the thermal polymerization initiator include at least one compound selected from the group consisting of benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, t-butyl peroxy-2-ethyl-hexanoate, cumyl hydroperoxide, and hydrogen peroxide, 2,2'-azobis(2-cyanobutane), 2,2'-azobis(methylbutyronitrile), 2,2'-azobis(isobutyronitrile) (AIBN), and 2,2'-azobisdimethyl-valeronitrile (AMVN).

[0100] The polymerization initiator can be decomposed by heat at 30°C to 100°C in the secondary battery or by light such as UV at room temperature (5°C to 30°C) to form radicals, and cross-linking bonds can be formed by free radical polymerization to polymerize the oligomer.

[0101] The second oligomeric compound can be the same type of first oligomeric compound as described above. The first oligomeric compound and the second oligomeric compound can be the same or different.

[0102] Specifically, the second oligomer compound may include at least one selected from the group consisting of polyether-based oligomers, polycarbonate-based oligomers, acrylate-based oligomers, polysiloxane-based oligomers, phosphagene-based oligomers, polyethylene-based oligomers, urethane-based oligomers, epoxy-based oligomers, fluorine-based oligomers, polyethylene oxide, polyester sulfide, polyvinyl alcohol, and polyvinylidene fluoride, specifically at least one selected from fluorine-based oligomers, polycarbonate-based oligomers, and polysiloxane-based oligomers.

[0103] For example, the fluorine-based oligomer may specifically include a unit derived from a fluorine-based monomer. The fluorine-based oligomer has an advantage that the fluorine-based functional group contained therein suppresses the generation of oxygen radicals caused by the decomposition of the positive electrode active material, thereby further improving battery stability and having excellent flame retardancy. More specifically, the fluorine-based oligomer may include at least one selected from tetrafluoroethylene (TFE)-vinyl acetate copolymer, (allyl 1,1,2,2-tetrafluoroethyl ether)-(2,2,2-trifluoroethyl acrylate) copolymer, tetrafluoroethylene-(2-vinyl-1,3-dioxolane) copolymer, and tetrafluoroethylene-vinyl methacrylate copolymer.

[0104] In addition, the polycarbonate oligomer has an affinity for the positive electrode, has a structure similar to that of an organic electrolyte, and has the advantage of being excellent in ion conductivity or ion dissociation degree.

[0105] In addition, the polysiloxane oligomer can function as a scavenger for gases (such as HF) generated by side reactions of the electrolyte, thereby improving high-temperature storage characteristics.

[0106] The weight average molecular weight of the second oligomer compound may be from 1,000 g / mol to 50,000 g / mol, specifically from 4,500 g / mol to 30,000 g / mol.

[0107] The second oligomer compound may be included in the gel polymer electrolyte composition in an amount of 1 wt% to 20 wt%, specifically 3 wt% to 10 wt%, and within this range, the effect of improving the cell rigidity of the secondary battery may be excellent, and the ion conductivity and lithium ion mobility of the gel polymer electrolyte may be excellent. The organic solvent may be used for dissolving or dispersing the lithium salt and the second oligomer compound.

[0108] The organic solvent is one that is commonly used in secondary batteries, and for example, ethers, esters (acetates, propionates), amides, linear or cyclic carbonates, nitriles (acetonitrile, SN, etc.), etc., can be used alone or in combination of two or more.

[0109] Among them, typically, carbonate-based solvents containing a carbonate compound such as a cyclic carbonate, a linear carbonate, or a mixture thereof can be used as the first solvent.

[0110] Specific examples of the cyclic carbonate compound include a single compound or a mixture of at least two selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, and halides thereof. Specific examples of the linear carbonate compound include a compound or a mixture of at least two selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC), but are not limited thereto.

[0111] In particular, among the carbonate-based solvents, propylene carbonate and ethylene carbonate, which are cyclic carbonates, are preferably used since they are high-viscosity organic solvents with high dielectric constants and can easily dissociate lithium salts in the electrolyte. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as ethyl methyl carbonate, diethyl carbonate, or dimethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be obtained, and therefore the cyclic carbonates can be more preferably used.

[0112] Among the organic solvents, the ester may be a single compound or a mixture of at least two kinds selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, α-valerolactone, and ε-caprolactone, but is not limited thereto.

[0113] The first oligomer compound may be dissolved in the gel polymer electrolyte composition by injecting the gel polymer electrolyte composition. Specifically, the first oligomer compound used in assembling the electrode assembly may be dissolved in the gel polymer electrolyte composition by injecting the gel polymer electrolyte composition. As described below, the first oligomer compound is polymerized when the gel polymer electrolyte composition is cured.

[0114] The dissolution of the first oligomer compound may be more smoothly performed by applying pressure in the activation and degassing processes generally involved in the secondary battery manufacturing process. The activation is a process of forming a solid electrolyte interface layer (SEI layer) on the surface of the electrode plate of the electrode assembly by a charging process in an initial secondary battery, thereby making the secondary battery supply electric power, and may be performed at a temperature of, for example, 45° C. or higher, specifically, 50° C. to 70° C. The degassing process is a process of discharging gas generated in the activation process to the outside, and may include a process of pressurizing the secondary battery using a jig or the like in the degassing process. The first oligomer compound may be more smoothly dissolved or removed by such temperature increase and pressure.

[0115] The gel polymer electrolyte composition 200 is poured into a battery case 300, and the electrode assembly 100 is impregnated with the gel polymer electrolyte composition 200. The impregnation may be performed at a temperature of 10° C. to 30° C. for 0.5 to 72 hours, and preferably at a temperature of 15° C. to 30° C. for 40 to 60 hours.

[0116] (4) Curing step of the gel polymer electrolyte composition The gel polymer electrolyte composition 200 is then cured, as shown in Figure 10. Specifically, the gel polymer electrolyte composition 200 is cured to form a gel polymer electrolyte 200a.

[0117] When the gel polymer electrolyte composition is cured, the oligomer compound is crosslinked and cured to form a gel-like solidified electrolyte (gel polymer electrolyte). Specifically, the second oligomer compound contained in the gel polymer electrolyte composition and the first oligomer compound dissolved by the gel polymer electrolyte composition are crosslinked or polymerized with each other by the curing process to form a gelled electrolyte.

[0118] The gel polymer electrolyte formed by curing the gel polymer electrolyte composition can help improve the cell rigidity of a secondary battery. As described above, the separator according to the present invention can help reduce resistance by including a ceramic coating layer using a low content of binder. As a result, a secondary battery in which the separator and the gel polymer electrolyte are combined can simultaneously reduce resistance and improve cell rigidity.

[0119] Here, the gel polymer electrolyte composition may be cured at a temperature of 50° C. to 100° C. for 0.5 to 48 hours, and preferably at a temperature of 60° C. to 80° C. for 0.5 to 24 hours.

[0120] Meanwhile, the curing may be performed in a sealed state of the battery case 300. For example, the electrode assembly 100 and the battery case 300 containing the gel polymer electrolyte composition 200 may be sealed with a cover, and then the gel polymer electrolyte composition may be thermally cured by heat treatment.

[0121] After the curing or sealing and curing, further steps such as activation, degassing, and resealing, which are known in the art, may be performed.

[0122] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a block diagram of a semiconductor device according to an embodiment of the present invention;

[0123] Examples and Comparative Examples Example 1 1. Manufacturing of separators Inorganic particles are Al2O3 (average particle size (D 50 A ceramic coating layer-forming composition was prepared by adding 100% cellulose acetate (0.5 μm) and an acrylic binder to a solvent, water, in a weight ratio of 96:4. As the acrylic binder, a mixture of TRD 202A manufactured by JSR and AP-0821 manufactured by APEC was used.

[0124] The composition for forming a ceramic coating layer was applied by gravure coating to both sides of a polyethylene porous substrate (thickness: 9 μm, average pore size: 0.05 μm, porosity: 45% by volume) and dried to form a ceramic coating layer (thickness of one layer: 1.5 μm), thereby producing a separator (thickness: 12 μm = 1.5 μm + 9 μm + 1.5 μm).

[0125] 2. Manufacturing the electrode assembly The separator reel on which the separator was wound was unwound, and the separator was placed on a table. An adhesive was applied onto the separator in a pattern of a plurality of dots spaced apart from each other using a first nozzle. As the adhesive, polycarbonate (weight average molecular weight Mw: 20,000) was used as a first oligomer compound. Thereafter, the positive electrode sheet was unwound from the first electrode reel on which the separator was wound, and cut with a first cutter to manufacture a positive electrode. The positive electrode was transported by a first transport device and adsorbed onto a first header. The first header was moved to the table side, and the positive electrode was attached onto the separator.

[0126] The table was then moved to the side and the separator was folded to one side to cover the positive electrode.

[0127] Next, the same adhesive as that used above was applied to the surface of the separator (the surface opposite to the surface where the separator and the positive electrode were in contact) using a second nozzle in a pattern of multiple dots spaced apart from each other.

[0128] Next, the negative electrode sheet was unwound from the second electrode reel and cut with a second cutter to produce a negative electrode, and the negative electrode was transported by a second transport device and attached to a second header. The second header was moved to the table side, and the negative electrode was attached to the surface of the separator (the surface opposite to the surface where the separator and the positive electrode contact each other).

[0129] Next, the table was moved laterally again, and the separator was folded to the other side to cover the negative electrode.

[0130] The above process was repeated several times to manufacture an electrode assembly in which 18 basic units each having a separator / positive electrode / separator / negative electrode stacked in sequence were stacked, in which the separator was folded in a zigzag shape.

[0131] Here, in the case of the positive electrode, the positive electrode active material is Li[Ni 0.8 Co 0.1 Mn 0.1 A positive electrode slurry was prepared by adding 1,02-tetrafluoroethylene (1,3-dimethylphenyl)-2 ...

[0132] In addition, in the case of the negative electrode, graphite as a negative electrode active material, styrene-butadiene rubber as a binder, carbon black as a conductive material, and carboxymethyl cellulose (CMC) as a thickener were added to water as a solvent in a weight ratio of 95.5:2.5:1.0:1.0 to prepare a negative electrode slurry, and the negative electrode slurry was applied to both sides of a copper current collector as a negative electrode current collector, which was then dried and rolled to form a negative electrode active material layer.

[0133] 3. Preparation of Gel Polymer Electrolyte Composition The gel polymer electrolyte composition was produced by mixing a polycarbonate-based oligomer (weight average molecular weight Mw: 20,000) as an oligomer, LiPF6 as a lithium salt, and AIBN (Azobisisobutyronitrile) as a polymerization initiator in a solvent.

[0134] The solvent was a mixture of ethyl carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7, the lithium salt was contained in the gel polymer electrolyte composition at a concentration of 1.0 M, the oligomer was contained in the gel polymer electrolyte composition at 5 wt %, and the polymerization initiator was contained in the gel polymer electrolyte composition at 0.6 parts by weight relative to 100 parts by weight of the oligomer.

[0135] 4. Secondary battery manufacturing A pouch-type battery case made of aluminum was prepared as the battery case, and the electrode assembly was housed in the housing space of the battery case.

[0136] Next, a gel polymer electrolyte composition was injected into the battery case containing the electrode assembly, and the battery case was vacuum sealed after the injection of the gel polymer electrolyte composition.

[0137] By injecting the gel polymer electrolyte composition, the adhesive present in the electrode assembly was dissolved by the solvent of the gel polymer electrolyte composition.

[0138] Next, the gel polymer electrolyte composition injected into the battery case was cured by heat treatment at a temperature of 60° C. for 5 hours.

[0139] The battery case was then cooled, sealed and degassed to produce a secondary battery having a thickness of 0.8 cm.

[0140] Comparative Example 1 1. Manufacturing of separators The same separator as that produced in Example 1 was used.

[0141] 2. Manufacturing the electrode assembly An electrode assembly was produced in the same manner as in Example 1, except that polyvinylidene fluoride (PVdF) was used as the adhesive.

[0142] 3. Preparation of Gel Polymer Electrolyte Composition The same gel polymer electrolyte composition as in Example 1 was prepared.

[0143] 4. Secondary battery manufacturing Except for using the electrode assembly prepared above, a secondary battery was manufactured in the same manner as in Example 1. The thickness of the secondary battery was 0.8 cm.

[0144] Comparative Example 2 1. Manufacturing of separators Inorganic particles are Al2O3 (average particle size (D 50 ):0.5 μm) and PVdF as a binder were added in a weight ratio of 70:30 to acetone as a solvent to prepare a composition for forming a ceramic coating layer.

[0145] The composition for forming a ceramic coating layer was applied to both sides of a polyethylene porous substrate (thickness: 9 μm, average pore size: 0.05 μm, porosity: vol%) by gravure coating, and then dried to form a ceramic coating layer (thickness of one layer: 3 μm) to manufacture a separator (thickness: 15 μm = 3 μm + 9 μm + 3 μm).

[0146] 2. Manufacturing the electrode assembly A plurality of separators manufactured as described above were prepared. In addition, a plurality of positive electrodes and negative electrodes identical to those manufactured in Example 1 were prepared.

[0147] The first oligomer compound used as an adhesive in Example 1 was applied to one separator in a pattern of multiple dots spaced apart from each other. A positive electrode was attached to the separator. The first oligomer compound was applied to the positive electrode in a pattern of multiple dots spaced apart from each other, and another separator was attached to the positive electrode. Next, the first oligomer compound was applied to the separator in a pattern of multiple dots spaced apart from each other, and a negative electrode was attached to the separator.

[0148] The above process was repeated to manufacture an electrode assembly in which 18 basic units each having a separator / positive electrode / separator / negative electrode stacked in that order were stacked together. Here, the two separators in the basic unit were separate separators, and were not folded in a zigzag shape as in Example 1.

[0149] 3. Preparation of Gel Polymer Electrolyte Composition The same gel polymer electrolyte composition as in Example 1 was prepared.

[0150] 4. Secondary battery manufacturing Except for using the electrode assembly prepared above, a secondary battery was manufactured in the same manner as in Example 1. The thickness of the secondary battery was 0.8 cm.

[0151] Experimental Example 1.Resistance evaluation (1) Measurement of initial resistance For the secondary batteries of Example 1, Comparative Example 1, and Comparative Example 2, the initial resistance values ​​calculated using the voltage change (ΔV) measured when discharging at a 0.33 C rate (C rate) for 30 seconds at SOC 100% are shown in Table 1 below.

[0152] (2) Resistance measurement after 100 charge / discharge cycles The secondary batteries of Example 1, Comparative Example 1, and Comparative Example 2 were subjected to 100 cycles of charge and discharge under the following charge and discharge conditions. Table 1 shows the 100 cycle resistance values ​​calculated using the voltage change (ΔV) measured when discharging for 30 seconds at a 0.33 C rate with SOC 100%.

[0153] (3) Calculation of the rate of increase in resistance The resistance increase rate after 100 charge / discharge cycles was evaluated using the following formula, and is shown in Table 1 below.

[0154] Resistance increase rate (%) = (resistance after 100 cycles - initial resistance) / initial resistance x 100

[0155] 2. Evaluation of life performance The secondary batteries of Example 1, Comparative Example 1 and Comparative Example 2 prepared above were charged and discharged for 100 cycles at 45° C. under the following conditions, and the capacity retention rate after 100 cycles was evaluated.

[0156] *Charging and discharging conditions Charging: CC / CV mode; 0.33C; 4.2V, 1 / 20C cut-off Discharge: CC mode; 0.33C; 2.5V cut-off

[0157] The capacity retention rate was defined as the value obtained by dividing the discharge capacity for the 100th cycle by the discharge capacity for the first cycle under the above experimental conditions. The results are shown in Table 1 below.

[0158] 3. Cell Stiffness Measurement Using the 3-point bending method, a force was applied downward to the center of each secondary battery at a speed of 10 mm / min, and the stress value was measured when a displacement of 2 mm was given. Here, a preload of 30 gf was applied, the experiment was conducted at room temperature, and the stress value was measured using a universal testing machine (UTM). The results are shown in Table 1 below.

[0159] 4. Ignition temperature measurement test The secondary batteries of Example 1, Comparative Example 1, and Comparative Example 2 were fully charged to SOC 100%, then placed in a hot box and heated at a rate of 0.5°C / min. The ignition temperature was measured and is shown in Table 1.

[0160] [Table 1]

[0161] Referring to Table 1, it can be seen that the secondary battery manufactured in Example 1 has low resistance and resistance increase rate, high life characteristics, and excellent thermal stability.

[0162] On the other hand, the secondary battery of Comparative Example 1 exhibits a higher resistance and resistance increase rate than that of Example 1. This is believed to be because no oligomer compound was used as the adhesive used in manufacturing the electrode assembly.

[0163] In addition, the secondary battery of Comparative Example 2 uses both a separator containing a large amount of binder and a gel polymer electrolyte. As a result, the secondary battery manufactured in Comparative Example 2 has a much higher resistance and a much worse lifespan characteristic than that of Example 1. Meanwhile, the thermal stability of Comparative Example 2 is much worse, which is believed to be due to the fact that the content of inorganic particles in the separator is relatively low, and therefore the thermal shrinkage and short circuit of the separator cannot be sufficiently prevented. [Explanation of symbols]

[0164] 10 Secondary battery 100 electrode assembly U base unit 110 1st electrode 110a One end of the first electrode 120 2nd electrode 120a: one end of the second electrode 130 Separator 131 Porous substrate 132a, 132b ceramic coating layer 140 Applied adhesive 200 Gel polymer electrolyte 300 Battery Case 310 Cover 400, 500 electrode tab 610 First electrode reel 620 Second electrode reel 630 Separator reel 700 Tables 810 First Cutter 820 No. 2 Cutter 910 1st transfer device 920 Second transfer device 1010 First Header 1020 2nd Header 1101 First electrode sheet 1201 Second electrode sheet 1110 No. 1 nozzle 1120 No. 2 nozzle

Claims

1. manufacturing an electrode assembly in which electrodes and separators are alternately stacked, and an adhesive is applied to a surface of at least one of the electrodes and the separators to bond the electrodes and the separators to each other; housing the electrode assembly in a battery case; injecting a gel polymer electrolyte composition into the battery case to impregnate the electrode assembly; and curing the gel polymer electrolyte composition. the adhesive comprises a first oligomeric compound; The separator includes a porous substrate and a ceramic coating layer disposed on both sides of the porous substrate; The ceramic coating layer comprises 92% by weight or more and less than 100% by weight of inorganic particles and more than 0% by weight and 8% by weight or less of a binder; The gel polymer electrolyte composition comprises a lithium salt, an organic solvent, a polymerization initiator and a second oligomer compound.

2. By injecting the gel polymer electrolyte composition, the first oligomer compound is dissolved in the gel polymer electrolyte composition, The method for producing a secondary battery according to claim 1 , wherein the first oligomer composition is cured together with the gel polymer electrolyte composition when the gel polymer electrolyte composition is cured.

3. The method of claim 1 , wherein the adhesive is applied in a plurality of patterns spaced apart from each other.

4. The secondary battery according to claim 1 , wherein an area where the adhesive is applied is more than 0% and not more than 1% of an area of ​​a surface where the separator and the electrode are in contact with each other.

5. 2. The method for manufacturing a secondary battery according to claim 1, wherein the ceramic coating layer comprises 93% to 98% by weight of inorganic particles and 2% to 7% by weight of a binder.

6. The method for producing a secondary battery according to claim 1 , wherein the binder includes an acrylic binder.

7. 7. The method for producing a secondary battery according to claim 6, wherein the acrylic binder comprises at least one selected from the group consisting of a copolymer of ethylhexyl acrylate and methyl methacrylate; polymethyl methacrylate; polyethylhexyl acrylate; polybutyl acrylate; polyacrylonitrile; and a copolymer of butyl acrylate and methyl methacrylate.

8. The method for manufacturing a secondary battery according to claim 1, wherein the ceramic coating layer has a thickness of 0.1 μm to 10 μm.

9. The method for producing a secondary battery according to claim 1, wherein the separator has a thickness of 1 μm to 20 μm.

10. The secondary battery according to any one of claims 1 to 9, wherein the first oligomer compound and the second oligomer composition each independently comprise at least one selected from the group consisting of a fluorine-based oligomer, a polycarbonate-based oligomer, and a polysiloxane-based oligomer.

11. the electrodes include a first electrode and a second electrode; The method for manufacturing a secondary battery according to claim 1, wherein the electrode assembly is manufactured by a method including the following steps (a) to (f): (a) applying the adhesive to at least a portion of the separator and the first electrode; (b) adhering the separator and the first electrode with the applied adhesive; (c) folding one side of the separator to cover the first electrode; (d) applying the adhesive to at least a portion of the separator and the second electrode; (e) adhering the separator and the second electrode with the applied adhesive; and (f) folding the other side of the separator to cover the second electrode.

Citation Information

Patent Citations

  • Separator, battery, battery pack, electronic apparatus, electric vehicle, power storage device and power system

    JP2014182962A

  • Separator for secondary battery and lithium secondary battery including the same

    JP2021504914A

  • Lithium secondary battery and its manufacturing method

    JP2021504922A